PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK BERBANTUAN E-BOOK MAKER PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS II SD - Ridani Amalia; Dinda Yarshal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop digital-based learning media in the form of flipbooks supported by the E-Book Maker application (Heyzine Flipbooks) in the Pancasila Education subject for grade II Elementary Schools, focusing on the material "United Attitude to Protect the Environment". The background of this study is based on the low involvement and interest in learning of students due to the lack of utilization of interesting and interactive digital learning media in elementary school environments. Media development is carried out to answer the need for learning tools that are more contextual, visual, and easily accessible to students. The method used in this study is Research and Development (R&D) with the ADDIE model approach, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research instruments include validation questionnaires given to media experts, material experts, and response questionnaires from teachers and students. The results of the study showed that the developed flipbook media obtained a feasibility value from media experts of 90.5% and from material experts of 95%, both of which were in the "very feasible" category. In addition, the results of the practicality and effectiveness tests through teacher and student responses also showed that this media was easy to use, interesting, and able to improve students' understanding and interest in learning. Thus, flipbook learning media assisted by E-Book Maker can be an innovative solution in supporting the Pancasila Education learning process in elementary schools, especially in creating a more interactive and enjoyable learning experience.